Using an FSDS‐R Item to Screen for Sexually Related Distress: A MsFLASH Analysis. Issue 1 (18th December 2014) - Carpenter, Janet S.; Reed, Susan D.; Guthrie, Katherine A.; Larson, Joseph C.; Newton, Katherine M.; Lau, R. Jane; Learman, Lee A.; Shifren, Jan L.
Abstract Introduction The Female Sexual Distress Scale‐Revised (FSDS‐R) was created and validated to assess distress associated with impaired sexual function, but it is lengthy for use in clinical practice and research when assessing sexual function is not a primary objective. Aim The study aims to evaluate whether a single item from the FSDS‐R could be identified to use to screen midlife women for bothersome diminution in sexual function based on three criteria: (i) highly correlated with total scores; (ii) correlated with commonly assessed domains of female sexual functioning; and (iii) able to differentiate between women reporting high and low sexual concerns during the prior month. Methods Data from 93 midlife women were collected by the Menopause Strategies Finding Lasting Answers to Symptoms and Health (MsFLASH) research network. Main Outcome Measures Women completed the FSDS‐R, Female Sexual Function Index (FSFI), and Menopausal Quality of Life Scale (MENQOL). Those who reported a change in the past month on the MENQOL sexual were categorized into a high sexual concerns group, while all others were categorized into a low sexual concerns group. Results Women were an average of 54.6 years old (SD 3.1) and mostly Caucasian (77.4%), college educated (60.2%), married/living as married (64.5%), and postmenopausal (79.6%). The FSDS‐R item number 1 "Distressed about sex life" was: (i) highly correlated with FSDS‐R total scores (r = 0.90); (ii) moderately correlated with FSFI total scores (r = −0.38) and FSFI desire (r = −0.37) and satisfaction domains (r = −0.40); and (iii) showed one of the largest mean differences between high and low sexual concerns groups (P < 0.001). Other FSDS‐R items met one or two, but not all three of the prespecified criteria (i, ii, iii). Conclusions A single FSDS‐R item may be a useful screening tool to quickly identify midlife women with sexually related distress when it is not feasible to administer the entire scale, though further validation is warranted. Carpenter JS, Reed SD, Guthrie KA, Larson JC, Newton KM, Lau RJ, Learman LA, and Shifren JL. Using an FSDS‐R item to screen for sexually related distress: A MsFLASH analysis. Sex Med 2015;3:7–13.